The Relationship Between Postpartum Depression Risk and Emotional Intelligence and Evaluation of Affecting Factors - Şahin, Ayşegül; Soğukpınar, Neriman (Technium Social Sciences Journal, 2023)
Objective: This thesis research is a descriptive study conducted to evaluate the relationship between emotional intelligence and postpartum depression risk and the factors affecting it. Methods: The research was carried out between April 1 - September 30, 2018 at Katip Çelebi University Atatürk Training and Research Hospital, Obstetrics Clinic. The universe of the study consisted of women (N = 624) who gave birth between April 1 and September 30, 2018. The sample of the study consisted of 193 women who delivered at the Katip Çelebi University Atatürk Training and Research Hospital’s Obstetrics Clinic, agreed to participate in the research and complied with the research criteria. In the first meeting, the participants were applied “Participant Diagnosis Form” and “Schutte Emotional Intelligence Scale” and in the second meeting, “Edinburgh Postpartum Depression Scale” was applied in 6-8 weeks after birth. In the study, t-test was used in independent groups for differences in two-group variables, and ANOVA analysis was used in determining the differences in variables with more than two groups. Tukey analysis was used to determine which two groups differ from the variables determined as a result of ANOVA analysis. All analyzes were carried out through SPSS for Windows V25.0 package program. Results: In the study, the risk of postpartum depression was found to be 10.88%. No statistically significant relationship was found between postpartum depression risk and emotional intelligence (p> 0.05). There is a positive and weak relationship between the risk of postpartum depression and the evaluation of emotions from the sub-dimensions of emotional intelligence (p <0.05). There is no relationship between postpartum depression risk and emotional intelligence sub-dimensions, optimism and the use of emotions (p> 0.05). A statistically significant relationship was found between postpartum depression risk and relationships with spouse and marital satisfaction (p <0.05). Conclusion: At the end of the study, no significant relationship was found between emotional intelligence and postpartum depression. However, there are many studies in the world literature regarding the relationship between emotional intelligence and mental well-being. In our country, studies are needed in different groups.